Design and Implementation of Lab Scale Automated Solar Powered Irrigation and Fertigation System - Zaman, Khairul; Azizuddin, Muhammad; Morni, Abdul Azim; Zuhairah, Anisah; Khalil, Ashraf; Uddin, M. R.; Ang , Swee Peng (International Journal of Integrated Engineering, 2021)
In Brunei, natural oil and gas contributes to about 99% in the generation of electricity and about 88% to the country revenue. Since Brunei is heavily dependent on a non-renewable energy, potential exhaustion of oil and gas reserves pose a challenge to the country, especially with continuous increase of energy consumption in order to meet the population demand. Additionally, Brunei has ambition to improve its agriculture sector. Implementations of PV systems in local agricultural sectors can also help improving the country revenue by increasing yield and reducing costs from electricity consumption. In this paper, we present design and practical implementation of fully automated solar powered irrigation and fertigation system. Ultrasonic sensors and moisture sensors are used to detect the state of the tank and the soil. The whole system is controlled with a microcontroller and a wireless monitoring system with mobile application is designed. The operation of the system was tested and the performance was acceptable.